Charge Transfer from Quantum-Confined 0D, 1D, and 2D Nanocrystals - Li, Qiuyang; Wu, Kaifeng; Zhu, Haiming; Yang, Ye; He, Sheng; Lian, Tianquan (Chemical reviews, 2024)
The properties of colloidal quantum-confined semiconductor nanocrystals (NCs), including zero-dimensional (0D) quantum dots, 1D nanorods, 2D nanoplatelets, and their heterostructures, can be tuned through their size, dimensionality, and material composition. In their photovoltaic and photocatalytic applications, a key step is to generate spatially separated and long-lived electrons and holes by interfacial charge transfer. These charge transfer properties have been extensively studied recently, which is the subject of this Review. The Review starts with a summary of the electronic structure and optical properties of 0D–2D nanocrystals, followed by the advances in wave function engineering, a novel way to control the spatial distribution of electrons and holes, through their size, dimension, and composition. It discusses the dependence of NC charge transfer on various parameters and the development of the Auger-assisted charge transfer model. Recent advances in understanding multiple exciton generation, decay, and dissociation are also discussed, with an emphasis on multiple carrier transfer. Finally, the applications of nanocrystal-based systems for photocatalysis are reviewed, focusing on the photodriven charge separation and recombination processes that dictate the function and performance of these materials. The Review ends with a summary and outlook of key remaining challenges and promising future directions in the field.